Sierpinski carpet fractal antenna (SCFA) for RFID applications / Nordin Ahmad Khalid - Ahmad Khalid, Nordin
This work presented the design, simulation and analysis of Sierpinski carpet fractal antenna (SCFA) for Radio Frequency Identification (RFID) application. This prototype antenna was fabricated on RT Duroid 4350 of dielectric constant, e, = 3.48 with thickness of 1.524 mm while the center frequency was 5.8 GHz and using microstrip line feed. The commercial electromagnetic simulator, CST Microwave Studio was used to carry out the design and simulation. The prototype SCFA was realized and the measurement and analysis was carried out using Vector Network Analyzer (VNA) and Antenna Training System (ATS). Simulated and measurement values of the parameters of the antenna were compared. It was observed that the measured and simulated values of the parameters of the antenna were closed with each other and the omnidirectional radiation pattern was realized. The result shows that the fractal antenna is very small in size while keeping high radiation efficiency.